Fat and female fecundity: prospective study of effect of body fat distribution on conception rates. Issue 6876 (20th February 1993) - Zaadstra, B M; Seidell, J C; Van Noord, P A; te Velde, E R; Habbema, J D; Vrieswijk, B; Karbaat, J
Abstract : OBJECTIVES--To study the effect of body fat distribution in women of reproductive age on fecundity. DESIGN--Prospective cohort study of all women who had entered a donor insemination programme. SETTING--One fertility clinic serving a large part of the midwest of the Netherlands. SUBJECTS--Of 542 women attending the clinic for artificial insemination for the first time, 500 women were eligible for study. MAIN OUTCOME MEASURES--Probability of conception per cycle and number of insemination cycles before pregnancy or stopping treatment. RESULTS--A 0.1 unit increase in waist-hip ratio led to a 30% decrease in probability of conception per cycle (hazard ratio 0.706; 95% confidence interval 0.562 to 0.887) after adjustment for age, fatness, reasons for artificial insemination, cycle length and regularity, smoking, and parity. Increasing age was significantly related to lower fecundity (p < 0.05); very lean and obese women were less likely to conceive (p < 0.10) as were women with subfertile partners (p < 0.10). All other exposure variables were not significantly related to fecundity. CONCLUSIONS--Increasing waist-hip ratio is negatively associated with the probability of conception per cycle, before and after adjustment for confounding factors. Body fat distribution in women of reproductive age seems to have more impact on fertility than age or obesity.